2023
DOI: 10.3389/fpls.2023.1122742
|View full text |Cite
|
Sign up to set email alerts
|

Biochar amendment alters root morphology of maize plant: Its implications in enhancing nutrient uptake and shoot growth under reduced irrigation regimes

Abstract: IntroductionBiochar amendment provides multiple benefits in enhancing crop productivity and soil nutrient availability. However, whether biochar addition affects root morphology and alters plant nutrient uptake and shoot growth under different irrigation regimes remain largely unknown.MethodsA split-root pot experiment with maize (Zea mays L.) was conducted on clay loam soil mixed with 2% (w/w) of wheat-straw (WSP) and softwood (SWP) biochar. The plants were subjected to full (FI), deficit (DI), and alternate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 60 publications
(66 reference statements)
2
8
0
Order By: Relevance
“…On the one hand, biochar possesses a high specific surface area, and is also rich in mineral components that enable it to absorb soil nutrients directly, thereby reducing nutrient loss [37,38]. On the other hand, biochar can stimulate the activity of soil microorganisms and improve the soil microbiological environment, which is beneficial for promoting crop root growth and yield formation [39][40][41]. The findings of the present investigation suggested an inhibition of yield at the highest doses of mineral fertilizer (CF90B).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, biochar possesses a high specific surface area, and is also rich in mineral components that enable it to absorb soil nutrients directly, thereby reducing nutrient loss [37,38]. On the other hand, biochar can stimulate the activity of soil microorganisms and improve the soil microbiological environment, which is beneficial for promoting crop root growth and yield formation [39][40][41]. The findings of the present investigation suggested an inhibition of yield at the highest doses of mineral fertilizer (CF90B).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, biochar application, particularly WSP, enhanced soil available nutrient pools. All these beneficial effects contributed to improved plant nutrient uptake and shoot growth consequently enhanced plant biomass accumulation (Wan et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Partial root-zone drying (PRD) irrigation is a modification of DI that involves irrigating only part of the root system while allowing the rest of the roots experiencing soil drying, and the irrigation side is swapped in frequency depending on the soil moisture and crop water status (Kang and Zhang 2004). Studies on many crop species have shown that PRD could save irrigation water and outperform DI in terms of maintaining yields and improving WUE (Sepaskhah and Ahmadi 2010;Wang et al 2012Wang et al , 2017Wan et al 2023). Moreover, the drying/rewetting cycles of the soil under PRD could result in the "Birch effect" (Birch 1958), stimulating the mineralization of soil organic matter, thereby increasing soil N bioavailability and crop N uptake (Wang et al 2010a, b, c;Wang et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Surjan system directs irrigation water into channels between the beds by irrigating the beds for a long time, generally used for cultivating shallots in rice fields [1]. As a result, creative irrigation techniques are needed to reduce irrigation water consumption, boost plant water-use effectiveness (WUE), and minimally affect crop yield [2]. Above all, using a combination of biofertilizer and In an intercropping system, N2 (45 kg ha−1 N) is a feasible method to gradually raise crop grain output and sustain soil productivity [3].…”
Section: Introductionmentioning
confidence: 99%
“…Since the demand for shallots rises annually, more agricultural areas must be added to enhance production [2]. However, currently, agricultural land in Indonesia is getting narrower every year due to the conversion of land into non-agricultural land such as industry, settlements, and transportation routes, this makes the productivity of horticultural crops lower.…”
Section: Introductionmentioning
confidence: 99%